Neonatal Respiratory Distress Syndrome: Early Diagnosis, Prevention, and Treatment - S. A. Perepelitsa; A. M. Golubev; V. V. Moroz (Общая реаниматология)
to improve treatment results in premature infants with neonatal respiratory distress syndrome (NRDS), by establishing developmental mechanisms and elaborating methods for its early diagnosis, treatment, and prevention. Material and methods. The paper analyzes the results of a clinical observation and laboratory, instrumental, immunological, morphological, and radiological studies of 320 premature neonates at 26—35 weeks gestational age. The following groups of neonates were identified: 1) 40 premature neonatal infants without NRDS and with the physiological course of an early neonatal period (a comparison group); 2) 190 premature neonates with severe NRDS in whom the efficiency of therapy with exogenous surfactants, such as surfactant BL versus curosurf, was evaluated; 3) 90 premature newborn infants who had died from NRDS at its different stages. Results. The poor maternal somatic, obstetric, and gynecological histories in the early periods of the current pregnancy create prerequisites for its termination, favor the development of severe acute gestosis, and cause abnormal placental changes. Each gestational age is marked by certain placental changes that promote impaired uterineplacentalfetal blood flow and premature birth. Alveolar and bronchial epithelial damages, including those ante and intranatally, microcircula tory disorders play a leading role in the tanatogenesis of NRDS. Intranatal hypoxia and amniotic fluid aspiration are one of the important factors contributing to alveolar epithelial damage and NRDS in premature neonates. Exogenous surfactants prevent the development of hyaline membranes and are useful in the normalization of ventilation-perfusion relationships and lung biomechanical properties. Conclusion. This study could improve the diagnosis and treatment of NRDS, which assisted in reducing the duration of mechanical ventilation from 130±7.6 to 65±11.6 hours, the number of complications (the incidence of intragastric hemorrhages decreased from 28.8 to 9%), the stay length of the neonates in an intensive care unit, and early neonatal mortality rates from 9.3 to 0.9‰ and in improving demographic indicators.